World book 2001 (Chicago World Book, 2000)
Contains every article from The World Book Encyclopedia plus thousands more, extensive multimedia including videos, maps, 360-degree panoramas, photographs, sound, animations and simulations, World Book Dictionary, Research Wizards, "Surf the Millennium" on simulated Web sites for each century, one-year subscription to World Book Online (internet access required), online encyclopedia updates (internet access required).
System requirements: Microsoft Windows 2000, 98, 95, or NT4.0 or higher, Pentium-based PC or 100% compatible computer, 16 MB RAM (32 MB recommended; Windows 2000 requires 64 MB), 40 MB free hard disk space, 16-bit sound card, 16-bit colour recommended, CD-ROM drive (2x speed or faster), mouse.
Keywords: Encyclopedias and dictionaries -- Interactive multimedia